Context‐dependent dispersal determines relatedness and genetic structure in a patchy amphibian population. Issue 20 (7th September 2021) - Unglaub, Bianca; Cayuela, Hugo; Schmidt, Benedikt R.; Preißler, Kathleen; Glos, Julian; Steinfartz, Sebastian
Abstract: Dispersal is a central process in ecology and evolution with far reaching consequences for the dynamics and genetics of spatially structured populations (SSPs). Individuals can adjust their decisions to disperse according to local fitness prospects, resulting in context‐dependent dispersal. By determining dispersal rate, distance and direction, these individual‐level decisions further modulate the demography, relatedness and genetic structure of SSPs. Here, we examined how context‐dependent dispersal influences the dynamics and genetics of a great crested newt ( Triturus cristatus ) SSP. We collected capture–recapture data of 5564 individuals and genetic data of 950 individuals across an SSP in northern Germany. We added genetic data from six sites outside this SSP to assess genetic structure and gene flow at a regional level. Dispersal rates within the SSP were high but dispersal distances were short. Dispersal was context‐dependent: individuals preferentially immigrated into high‐quality ponds where breeding probabilities were higher. The studied SSP behaved like a patchy population, where subpopulations at each pond were demographically interdependent. High context‐dependent dispersal led to weak but significant spatial genetic structure and relatedness within the SSP. At the regional level, a strong hierarchical genetic structure with very few first‐generation migrants as well as low effective dispersal rates suggest the presence of independent demographic units. Overall, our study highlights the importance of habitat quality for driving context‐dependent dispersal and therefore demography and genetic structure in SSPs. Limited capacity for long‐distance dispersal seems to increase genetic structure within a population and leads to demographic isolation in anthropogenic landscapes.